Intra-cavity measurement concept of dispersion properties with a tunable fiber-integrated laser. (4th January 2019) - Tiess, Tobias; Hartung, Alexander; Becker, Martin; Chojetzki, Christoph; Rothhardt, Manfred; Bartelt, Hartmut; Jäger, Matthias
Abstract: The dispersion properties of fibers depict a key characteristic to model the propagation of ultra-short pulses in waveguides. In the following, a new method is presented to directly measure the dispersion properties of fibers and optical components in the time domain. The analysis is based on pulse shape variations along the tuning range of a theta cavity fiber laser (TCFL) depending on the adjusted repetition rate. The automated measurement procedure, evaluating pulse symmetry, achieves a temporal sensitivity below 5 ps surpassing the resolution of the acquisition electronics. Exemplarily, two samples of Nufern PM980-XP fiber are investigated with an Yb-doped tunable TCFL retrieving the mean dispersion parameter by comparative measurements. The obtained results are compared to a reference method based on spectral interferometry. With deviations in between either approach of and, respectively, the results agree well within the measurement errors of the TCFL, verifying the presented concept. Due to the pulse formation process extending over multiple round trips, this approach achieves an enhanced sensitivity compared to competing direct temporal methods. Together with an alignment free operation, the fiber-integrated TCFL depicts a simple and robust concept showing potential in specific measurement scenarios such as in quality management.